ALUR KERJA ECG pada PASIEN MONITOR - Hery Setiawan Gulo; Siti Rahmah (JURNAL MUTIARA ELEKTROMEDIK, 2020)
An electocardiogram (ECG) is one of the parameters in the patient monitor tool that is used to monitor the patient's physiological condition in the form of blood pressure, temperature, respiration, SpO2 and the shape of the heart pulse continuously. This study aims to determine the workflow of the ECG in monitor patients and to determine changes in the ECG waveform when the lead position is changed.This research was conducted at the USM-I Integrated Laboratory. The research method used was descriptive by observation. Which aims to find out how the ECG workflow on the patient monitor and to find out the changes in the ECG waveform when the lead position is changed.This research was conducted using the PM5000 patient monitor. The results of this study indicate that the electrical potential originating from the heart is detected on the surface of the body through electrodes and jelly, both of which are connected to the device via a patient cable in the form of a color coded lead on each lead, after amplifying then the electric pulse will be displayed on the display in the form wave. when installing the lead on the patient must be in accordance with the position and position according to the procedure, because it greatly affects the resulting wave.